Carandiru: the uses of a massacre’s memory (Revista Tempo e Argumento, 2017)
The Carandiru massacre, which took place in 1992, ischaracterized as a symbolic landmark in the historyof the Brazilian penal system. The recollection ofthis past talks to issues like the dimension of whathappened, impunity, the attempt to erase andshape memory, and the institution of massacre as ametaphor for new tragedies. In this process, we canobserve the construction of two possible pasts: oneundertaken by the State, establishing an officialmemory, and the other linked to various segmentsof organized civil society. I analyze the uses of thismemory and its recollection strategies, and thesecategories are understood through the history ofthe present time and the public history.Keywords: Carandiru; Memory; Public History;History of the Present Time.